(untitled) (MAUSAM, 2023)
This study assessed the climate change impacts on productivity for major rabi and kharif in Punjab. We compiled data for 35 years (1986–2020) using 5 crops across Punjab to estimate the impact of climate change by using temperature and rainfall. Our results indicate that productivity decreases with an increase in average temperature in most of the crops. The adverse impact of climate change on agricultural production indicates food security threat to farming community. The findings of the study suggest to focuses on the climate-smart agriculture for effective solution to climate risks.